Leveraging on Blockchain Technology for the Sustainability of Real Estate Practice: A Systematic Review - Oluwumni, Adedamola (Journal of African Real Estate Research, 2023)
Blockchain technology (BCTech) in real estate is innovative and full of potential, even though it is not widely accepted and scarcely applied. To establish the potentials of BCTech in the real estate sector, this study used a systematic review of the literature found in Researchgate, ScienceDirect, Semantic Scholar, IEEE Xplore, and Google searches. This was done with a view to ascertaining the current challenges in real estate practice and the potential benefits of applying BCTech to mitigate or eliminate these challenges. A total of 99 publications from 2016 to 2022 were examined, and their contents were assessed using descriptive statistical tools and presented in charts and tables. Based on the review, BCTech can provide platforms for tokenized ownership, smart contracts, quick transactions and cost reduction. Moreover, the outcome also showed that some countries have applied BCTech to land registration, with a few others to record keeping and real estate tokenization. In addition, the majority of the research efforts (55%) were from journal outlets published between 2020 and 2022. Finally, BCTech offers secure and transparent platforms for real estate stakeholders; hence, they have a lot to gain by encouraging and embracing its adoption. The study concluded that though BCTech is not yet widely used, it has a lot of potential to offer in terms of the sustainability of the real estate industry.